Risks in conservation heritage projects - Che Haron, Roziha; Mohd Nawi, Hadirah; Mustapha, Nur Fatihah (2019)
Risks in conservation projects are believed to be different from risks in new building projects. There are different methods and processes that need to be adopted in order to handle a conservation heritage endevaour, particularly in heritage projects. Heritage projects form a valuable inheritance with sentimental values that tell a certain history, culture or tradition which needs to be preserved. Nevertheless, due to limited knowledge on conservation heritage projects, project teams tend to treat a conservation project the same as a new building project. Many have reported that conservation projects frequently suffer failures in meeting the delivery goals of time, quality and budget, which lead to contractual disputes during the post-contract stages of a conservation project. Conservation work is riskier due to the inclusion of many activities such as preservation, restoration, and refurbishment. Thus, this research aims to identify the risks in carrying out conservation projects through conducting semi- structured in depth interviews and using the survey research method. The objectives are to make comparisons between the charateristics of new construction projects and conservation heritage projects, and identification of risks in conservation of heritage buildings. The outcome of this research is considered to be significant and relevant as it contributes towards the conservation sector by minimising the risks taken on conservation projects by the project team involved.